Co‐Occurrence of Apathy and Impulsivity in Progressive Supranuclear Palsy. Issue 8 (16th September 2021) - Kok, Zi Q.; Murley, Alexander G.; Rittman, Timothy; Rowe, James; Passamonti, Luca
ABSTRACT: Background: Apathy and impulsivity are common consequences of progressive supranuclear palsy (PSP) and can worsen its prognosis. They can co‐exist in the same patients although their concomitant prevalence remains unclear. Their relationship to emotional lability is unknown. Objectives: To estimate the co‐occurrence of apathy and impulsivity and their relationship to emotional lability in PSP. To characterize the demographic, clinical, and cognitive features of PSP patients with apathy and impulsivity. Methods: In a retrospective study of a long‐term clinical cohort, we assessed the prevalence of apathy, impulsivity, and emotional lability from clinical interviews, medical records, and contemporary carer questionnaires. One hundred fifty‐four patients with a diagnosis of probable or possible PSP (according to the 2017 Movement Disorder Society criteria) were identified. Sixty‐four of these patients had neuropathological confirmation of PSP. PSP patients with both apathy and impulsivity were compared in terms of demographic, clinical, and cognitive characteristics to PSP patients with either one or neither of these neuropsychiatric features. Results: Apathy and impulsivity co‐existed in two‐thirds of people with PSP. A fifth displayed emotional lability in addition to apathy and impulsivity. Apathy and impulsivity were more commonly co‐expressed than by chance. There was no single demographic, clinical or cognitive feature that distinguished between PSP patients with versus patients without apathy and impulsivity. Conclusions: The co‐existence of apathy and impulsivity in PSP suggests that these neuropsychiatric features may share similar risk factors and etio‐pathogenetic mechanisms. Apathy and impulsivity should be jointly assessed when planning symptomatic treatments for detrimental behavioral problems caused by PSP.